Redescription of Serpinema octorugatum (Baylis, 1933) (Nematoda: Camallanidae) from the Malayan box turtle Cuora amboinensis (Daudin) (Chelonia: Bataguridae) - Sharma, R.S.K.; Rigby, M.C.; Sumita, S.; Sani, R.A.; Vidyadaran, M.K.; Jasni, S.; Dailey, M.D. (Springer Science and Business Media LLC, 2002)
We redescribe the camallanid nematode Serpinema octorugatum (Baylis, 1933) from the box turtle Cuora amboinensis (Daudin) collected in Malaysia. In this redescription, we amend the original description by noting that there are only four cephalic papillae and that there are five pairs of post-anal papillae, and propose that the name of this species be corrected from S. octorugatus to S. octorugatum. Additionally, we removed the tissues overlying the buccal capsule and have used SEM studies to show that the peribuccal shields extend laterally from the buccal capsule, forming a surface possibly used in muscle attachment. Furthermore, we show that the supposedly non-cuticularised cylinder connecting the buccal capsule to the oesophagus in the Camallanidae is part of the buccal capsule and is, therefore, likely to be cuticularised. We also examine morphological measurements of taxonomic interest for correlations with total body length and find that many characters traditionally used for inter- and intra-specific comparisons are correlated with total body length in adult female worms. This suggests that comparisons between samples of adult female worms that do not account for the potential effect of total body length may be misleading. However, we show that some features of taxonomic interest are not correlated with total body length.